Increased expression of Prothymosin-α, independently or combined with TP53, correlates with poor prognosis in colorectal cancer - Zhang, Meng (e-Century Publishing Corporation, 2014)
Human prothymosin-α (PTMA) plays an important role in tumorigenesis, and its overexpression triggers a TP53 response. In this study, we identified that PTMA expression was up-regulated at both the transcriptional and translational level in tumor tissue compared to that in adjacent normal tissue. PTMA overexpression was significantly associated with the depth of tumor invasion, lymph node metastasis (LNM), distant metastasis, advanced AJCC stage, and tumor differentiation. There was also a significant association between PTMA over-expression and mutant TP53 expression (r=0.515, P < 0.001). Survival analysis revealed that the disease-free survival (DFS) and overall survival (OS) rates were significantly lower among patients with PTMA- and TP53-positive tumors. Hence, PTMA might play an important role in the progression of CRC, and the assessment of both PTMA and mutant TP53 expression can help predict colon cancer prognosis.